Missing in Sydney - Hutchinson, Andrea M.; Ponzi, Emiliano (Genoa, Italy : Black Cat Pub., 2006)
An illustrated graded reader about three best friends in search of adventure in Sydney, Australia; with activities to promote language skills, tests with answer key, and a CD recording of the text.
"Step One, A2"--Cover.
Compact disc.
Young Adult
Keywords: Readers; Compact discs; Reading materials; Compact discs